The exemplar interleaving effect in inductive learning : Moderation by the difficulty of category discriminations - Norehan, Zulkiply; Burt, Jennifer S. (Springer-Verlag, 2013)
Recent research demonstrates a spacing effect in inductive learning. Spacing different individual exemplars apart in time rather than massing them together aids in the learning of categories. Experiment 1 examined whether it is interleaving or temporal spacing that is critical to the spacing effect in the situation when the memory load is high, and the results favoured interleaving. Experiment 2 examined the effect of the difficulty of the category discrimination on presentation style (massed vs spaced) in inductive learning, and the results demonstrated that spacing (i.e., interleaving of exemplars from different categories) is advantageous for low-discriminable categories, whereas massing is more effective for high-discriminable categories. In contrast to these performance measures, massing was judged by participants to be more effective than spacing in both discriminability conditions, even when performance for low discriminable categories showed the opposite.